2017
DOI: 10.22334/jbhost.v2i1.65
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Aceh Traditional Culinary as Tourist Attractions

Abstract: In recent time, tourism industry has not only been one of the rapidly growing fields of the world economy, but also has brought about economy development for diverse states and regions. Food is one of the principal factors are items that have been neglected in the most of the studies. To survive, in the first place, every tourist as an organism need to eat and drink and the uniqueness of culinary make it more interest them. We choose Aceh because it is one of the provinces in Indonesia which has a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The influence of India can mostly be seen in the dishes that are generally cooked by the people of Aceh which are made from beef, such as meat curry dishes that use lots of spices such as cloves and nutmeg as well as those used in Indian cuisine [ 52 ]. Curry is a type of dish made from beef or mutton that is often cooked by Aceh beef consumers [ 9 ] and is also one of the main types of cuisine in Aceh Province [ 53 , 54 ]. Apart from curry, there are other types of dishes made from beef, including jerky, curry, kuwah beulangong, sie reuboh, and meat soup [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of India can mostly be seen in the dishes that are generally cooked by the people of Aceh which are made from beef, such as meat curry dishes that use lots of spices such as cloves and nutmeg as well as those used in Indian cuisine [ 52 ]. Curry is a type of dish made from beef or mutton that is often cooked by Aceh beef consumers [ 9 ] and is also one of the main types of cuisine in Aceh Province [ 53 , 54 ]. Apart from curry, there are other types of dishes made from beef, including jerky, curry, kuwah beulangong, sie reuboh, and meat soup [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Curry is a type of dish made from beef or mutton that is often cooked by Aceh beef consumers [ 9 ] and is also one of the main types of cuisine in Aceh Province [ 53 , 54 ]. Apart from curry, there are other types of dishes made from beef, including jerky, curry, kuwah beulangong, sie reuboh, and meat soup [ 53 ]. In the manufacturing process, all types of dishes undergo a relatively long boiling process [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Referring to the understanding of cultural heritage according to [9], the cultural heritage is both physical and nonphysical culture that is passed down from the previous generation to the next generation. Traditional food and beverage is one of the non-material cultural heritage that belongs to Indonesian people and one of the attractions of cultural heritage tourism, which is often called culinary tourism or gastronomic tourism [10]. The notion of gastronomic tourism is not only limited to food and beverages as the main tourist attraction, but also include everything related with food activities, ranging from the provision of food ingredients, preparation, cooking, serving, and cultural values inherent in these foods [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…[11] says that tourism is a threat to the preservation of cultural heritage because it will eliminate cultural values. Nevertheless, tourism is actually able to become a cultural heritage preserver [11]- [17] Gastronomic tourism as one of the attractions of tourism can be a preserver of the cultural heritage [1], [4], [5], [10], [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of them explore new potential culinary attraction, and some of them explore already exist culinary potentials. Turgarini, D., & Abdillah, F. (2017) in their research entitled Introducing Aceh Traditional Culinary as Tourist Attractions, the results obtained showed that Aceh has a varied culinary potential and very full featured, yet necessary efforts to familiarization some of food Aceh in the international community. Another thing is that most typical culinary Aceh is presented for ceremonial purposes that have not been commercialized.…”
Section: Introductionmentioning
confidence: 99%